PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING DENGAN MIND MAPPING DALAM UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI EKONOMI - Istikharo, ; Supono, (Pendidikan Ekonomi, 2013)
The observation and interview that done on the Economics teacher and so did the students in VIII-C, showed that the students learning outcome remained low. That was because the students hadnt find their effective learning yet, moreover the teacher tended to apply the speech and discussion method. Thus, they needed the learning strategies to answer their problem. One of the effective techniques that can be applied is the Quantum teaching with mind mapping. This study aimed to find out the class activity in applying the Quantum teaching method with Mind mapping to increase the students learning outcomes in Economics lesson. Moreover, this study also aimed to find out the students learning outcomes after applying this model. The type of this study is Class Action Research that done in two cycles. The result of the study shows that the implementation of Quantum Teaching learning model with Mind mapping had run effectively. The students and teacher activity were increased in each cycle. Furthermore, the test result shows that after applying the Quantum teaching learning model with Mind mapping, the students learning outcomes is increased in every cycle.